Static strengthening and fatigue blunt-notch sensitivity in low-carbon steels - Chapetti, Mirco Daniel (2001)
The influence of four different static strengthenings on the fatigue blunt-notch sensitivity of a low-carbon steel with a ferrite–pearlite microstructure was analyzed and modeled. The analysis was made using a model previously derived which estimates the fatigue limit of blunt notched components by means of the parameter ktd defined as the stress concentration introduced by the notch at a distance d from the notch root surface equal to the distance between microstructural barriers. While the distance d between microstructural barriers is kept constant by keeping constant the grain size, the effective resistance of the microstructural barriers to crack propagation is increased by static strengthening. The analyses have shown the influence of the distribution and effective resistance of the first two or three microstructural barriers on fatigue blunt-notch sensitivity.